Forensic Accounting & Auditing Techniques on Public Sector Fraud in Nigeria - EBIMOBOWEI, APPAH (2018)
The purpose of this paper was to empirically analyze the effect of forensic accounting and auditing techniques on public sector fraud detection, investigation and prevention in Nigeria. Specifically, the study sought to establish the effect of the various techniques of forensic accounting on public sector fraud and secondly, to determine the effect of forensic auditing on fraud detection, investigation and prevention. The research design used in this study was expost factor design. The study employed restructured questionnaire for data collection after validity and reliability with regression analysis for hypothesis testing. The study revealed that the relationship between forensic accounting and auditing techniques and public sector fraud detection, investigation and prevention in Nigeria is quite significant. The study therefore concludes that forensic accounting and auditing techniques is a major panacea to the level of fraudulent activities experienced in the Nigerian public sector. It was recommended among others that government should consider providing more fraud hotlines, improve the whistleblowing policy and establish forensic accounting department in the public sector in order to enhance the fraud detection, investigation and prevention mechanism in the public sector. The paper fills an important gap in academic literature by providing insights into the techniques of forensic accounting and auditing in developing economies. Keywords: Forensic Accounting, Auditing, Fraud, Public Sector